2021
DOI: 10.3390/nano11123439
|View full text |Cite
|
Sign up to set email alerts
|

Green Hydrogels Composed of Sodium Mannuronate/Guluronate, Gelatin and Biointeractive Calcium Silicates/Dicalcium Phosphate Dihydrate Designed for Oral Bone Defects Regeneration

Abstract: Innovative green, eco-friendly, and biologically derived hydrogels for non-load bearing bone sites were conceived and produced. Natural polysaccharides (copolymers of sodium D-mannuronate and L-guluronate) with natural polypeptides (gelatin) and bioactive mineral fillers (calcium silicates CaSi and dicalcium phosphate dihydrate DCPD) were used to obtain eco-sustainable biomaterials for oral bone defects. Three PP-x:y formulations were prepared (PP-16:16, PP-33:22, and PP-31:31), where PP represents the polysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Moreover, green chemistry-based biomaterials were also invented and utilized for oral bone regeneration. Gandolfi et al formulated a hydrogel consisting of polysaccharides (copolymers of L-guluronate and D-mannuronate) and peptide (gelatin) matrix activated with biominerals (calcium silicate, dicalcium phosphate dehydrate) type of fillers and evaluated this green hydrogel for bone regeneration [ 130 ]. Also, they had developed Poly-lactic acid (PLA) based scaffolds loaded in exosomes with suitable minerals (calcium silicate and dicalcium phosphate dehydrate; DCPD) to improve the osteogenic strength of human adipose-derived mesenchymal stem cells [ 131 ].…”
Section: Application Of the Nano Dentistrymentioning
confidence: 99%
“…Moreover, green chemistry-based biomaterials were also invented and utilized for oral bone regeneration. Gandolfi et al formulated a hydrogel consisting of polysaccharides (copolymers of L-guluronate and D-mannuronate) and peptide (gelatin) matrix activated with biominerals (calcium silicate, dicalcium phosphate dehydrate) type of fillers and evaluated this green hydrogel for bone regeneration [ 130 ]. Also, they had developed Poly-lactic acid (PLA) based scaffolds loaded in exosomes with suitable minerals (calcium silicate and dicalcium phosphate dehydrate; DCPD) to improve the osteogenic strength of human adipose-derived mesenchymal stem cells [ 131 ].…”
Section: Application Of the Nano Dentistrymentioning
confidence: 99%
“…However, increased osteoblast viability with decreased osteogenic differentiation is a common outcome for apatite layered materials [ 43 ]. With the other chemical characterization showing higher levels of CaP surface mineralization in this study, mineralization may not occur for several days in the SBF in vitro [ 58 , 61 , 62 , 63 , 64 ]. Several studies have shown that the process of mineralization may take time in SBF for mineral formation.…”
Section: Resultsmentioning
confidence: 74%
“…Moreover, calcium silicate biomaterials have been combined with natural polymers and collagen peptides due to their gradual resorption properties and the subsequent formation of apatite. In the literature, it has been reported that combinations such as gelatin methacryloyl (GelMA)/alginate/tri-calcium silicate and natural polysaccharides (copolymers of sodium D-mannuronate and L-guluronate)/natural polypeptides (gelatin)/calcium silicate/dicalcium phosphate dihydrate can be used to create an appropriate micro-environment for the regeneration and healing of oral bone defects [ 115 , 116 ].…”
Section: Bioceramicsmentioning
confidence: 99%